(untitled) (The Strategic Review for Southern Africa, 2020)
In light of recent developments such as the African Continental African Free Trade Area agreement (AfCFTA), incrementalist approaches to regional inte gration that focus on sub-regions seems to have been pushed to the backburner as more focus puts the entire African continent at the centre of integration processes. With all its potential, gradual macro-economic convergence has accordingly been neglected. Discussions on macro-economic convergence have on the other hand been cast over the broader sub-region such as the Southern African Development Community (SADC) where a number of indicators and targets have been identified and pursued closely. Whilst looking at Botswana as a point of departure, this paper argues that incremental macro-economic convergence is pivotal to broader regional integration and the Southern African Customs Union (SACU) provides an ideal stepping-stone. An incrementalist approach to macro-economic convergence as well as broader regional integration should begin with identifying key formal institutions that serve as custodians of macro-economic policy such as the central banks and departments of finance or treasuries. Using secondary data sources, with Botswana as a case study, this paper foregrounds macro-economic convergence, macro-economic policy making institutions, and SACU as critical building blocks for broader regional integration.